Beyond Riwayah-Dirayah : The Penta-Structural Hadith Studies As Edi Safris Epistemological Contribution - Qurrota A'yun; Arif Budiman; Sri Handayana (Al-Mu'tabar, 2026)
This article aims to analyse and reconstruct the epistemological ideas of Edi Safri, Professor of Hadith Studies at UIN Imam Bonjol Padang, which are formulated as the pentastructural study of hadith. Hadith studies in Indonesia and the Islamic world in general still rely on two major classifications: the science of hadith transmission (riwayah), which governs the transmission and preservation of hadith, and the science of hadith understanding (dirayah), which establishes the principles of sanad and matan criticism. Although both have made fundamental contributions to the Islamic scholarly tradition, this dualistic framework is not sufficient to depict the true breadth, depth, and contemporary relevance of hadith studies. There is a significant gap in the form of a void in the framework that integrates the dimensions of authenticity, historicity, hermeneutics, intellectual biography, and contemporary responses into a cohesive epistemological structure. This research employs a qualitative method with a descriptive-analytical approach and a biographical-intellectual study based on the author's direct involvement in the learning process with Edi Safri from the undergraduate to doctoral level (2012–present). The findings show that the pentastructural framework fills the epistemological gap left by classical classifications, integrating historical, hermeneutic, intellectual biography, and contemporary response dimensions into a coherent and pedagogically layered scientific architecture. The penta-structural framework of hadith studies includes: (1) al-bahṡ al-asāsī (main study/critique of chain-text), (2) al-bahṡ at-tārīkhī (historical study), (3) al-bahṡ ʻan al-fiqh al-ḥadīṡ (methodological study of hadith understanding), (4) al-bahṡ ʻan al-aʻlām wa al-muṣannafāt (study of figures and literature), and (5) al-bahṡ ʻan al-musykilāt wa al-ḥawādiṡ al-ḥadīṡiyyah (study of contemporary issues). This framework is relevant as an alternative methodology that is more holistic and systematic for the study of modern hadith in Indonesia and globally.